Effects of PU, USG and NPK briquette on nitrogen use efficiency and yield of BR22 rice under reduced water condition (Journal of the Bangladesh Agricultural University, 2014)
An experiment was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh during the aman season of 2012 to investigate the effects of prilled urea (PU), urea super granule (USG) and NPK briquette on NH4- N concentration in field water, yield and nitrogen (N) use efficiency (NUE) of BR22 rice under reduced water conditions. The experiment was laid out in a randomized complete block design with three replications. There were altogether eight treatment combinations viz. T1: Control (No N fertilizer), T2: 52 kg N ha-1 from USG, T3: 104 kg N ha-1 from USG, T4: 78 kg N ha-1 from PU, T5: 120 kg N ha-1 from PU, T6: 51 kg N ha-1 from NPK briquette, T7: 78 kg N ha-1 from USG and T8: 78 kg N ha-1 from NPK briquette. Water samples were collected from rice field for seven consecutive days after deep placement of USG and the first split application of PU and the samples were analyzed for NH4-N. The Highest concentration of NH4-N in water was observed at the second day of PU application followed by gradual decrease with time. The yield contributing characters like plant height, panicle length, number of effective tillers hill-1 and grains panicle-1 were significantly influenced by different treatments. The highest grain yield of 3.93 t ha-1 was recorded from 104 kg N ha-1 as USG (T3) and the lowest value of 2.12 t ha-1 was obtained from control. The N use efficiency was increased when the N was applied as USG. The overall results revealed that application of USG and NPK briquette may be practised for obtaining better yields in addition to increasing the efficiency of N fertilizer. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19897 J. Bangladesh Agril. Univ. 11(2): 215-220, 2013